A qualificação profissional no contexto da reestruturação produtiva: impactos no trabalho e nos trabalhadores - Machado, Marilene Salgueiro Berto (2012)
This study ―A QUALIFICAÇÃO PROFISSIONAL NO CONTEXTO DA REESTRUTURAÇÃO PRODUTIVA: impactos no trabalho e nos trabalhadores (O Cenário brasileiro nos anos de 1990)‖ [―THE PROFESSIONAL QUALIFICATION IN THE CONTEXT OF PRODUCTIVE RESTRUCTURING: impacts on work and workers (The Brazilian scenario in the 1990s‖], presents the doctoral thesis in the relationship Capital x Work, the productive restructuring process reiterates the alienation process of the working class by means of a new pattern of professional ―training‖ that goes beyond the old professional qualification pattern. It aims to discuss the professional qualification highlighting the working world scenario in the 1990s, in which the labor relations assume proportions increasingly relevant. The research analysis locus is the automotive sector for it is the one that more rapidly and in better way adapted to the restructured job requirements. FIAT-Minas was the enterprise chosen for analysis for it represents this sector in Brazil in an expressive way, due to maintaining in its structure a professional training school: the ISVOR/Fiat. The research was qualitative and developed an analytical-critical approach, theoretically based on the dialectical method, understood as a methodological possibility to analyze the study object, considering it in its totality. For its completion were done: bibliographic studies and analysis of the theoretical works, highlighting the contribution of such works in the discussion about professional qualification in Brazil, besides the social-economical and educational theories studies, statistical data studies, documents and reports. The theoretical category work and the human sociability conception were central for the study of the Brazilian automotive industry and FIAT Minas. The analysis carried out showed that the professional qualification has been used as a worker adaptation space in the government and enterprise proposals, and that Fiat Minas has been adopting since the 1990s. We conclude, therefore, that the defense of the professional qualification as a space of formal education, unified and emancipating for the worker still is a social challenge, seeking the establishment of an education that enables the human sociability